CRIMINAL LIABILITY FOR ARTIFICIAL INTELLIGENCE-BASED CRIMES UNDER CRIMINAL LAW IN INDONESIA - Hendri Saputra Manalu; Rahmadany; Anto Mutriady (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The development of Artificial Intelligence (AI) technology brings complex legal implications, particularly in the field of criminal law. Crimes committed using AI systems such as deepfakes, automated cyberattacks, algorithm-based fraud, and data manipulation raise fundamental questions about who should be held criminally responsible. This study aims to analyze the concept of criminal liability for AI-based crimes within the current Indonesian criminal law framework and identify existing legal gaps (leemten in het recht). The research method used is normative juridical with a statutory approach, a conceptual approach, and a comparative approach. The results show that the Criminal Code (KUHP) and Law Number 19 of 2016 concerning Information and Electronic Transactions (ITE) have not been able to optimally address criminal liability for crimes bridged by autonomous AI systems. Comprehensive regulatory reform is urgently needed, including the establishment of new legal subjects, the implementation of adapted doctrines of strict liability and vicarious liability, and the establishment of a specific legal framework related to AI. This study recommends the drafting of an Artificial Intelligence Bill that explicitly regulates aspects of criminal liability in the AI ecosystem.